Polarization Effect on Dual and Quad Output Fiber Laser Based on Sagnac Loop Mirror Interferometer - Abu Hasan N.N.; Sulaiman A.H.; Abdullah F.; Yusoff N.M.; Ismail A.; Jamaludin M.Z. (Taylor and Francis Ltd., 2025)
This work investigates the performance of dual and quad laser wavelengths at simultaneous angle adjustment of polarization controller based on a Sagnac loop mirror interferometer. From our observation, 13 m polarization maintaining fibers of PMF length performed better in terms of lasing lines, peak power and extinction ratio of 4, ?8 dBm and 38 dB, respectively. When the intensity increases, the flatness and number of channels are improved to prove that significant power setting for the best laser performance. The flatness and number of lasers are changed with the simultaneous adjustment of half-wave plate and quarter-wave plate angles. These dual and quad laser wavelengths have good power stability according to the low fluctuation below 2.25 dB of peak power difference on the laser peaks within 100 minutes. ? 2024 Taylor & Francis.